On Public Commands, Affections and Christian Nationalism - Hordern, Joshua (Studies in Christian ethics, 2026)
This concluding paper addresses some important themes in Joan Lockwood O?Donovan's English Public Theology, not considered in other papers in this special issue, but which take us to the heart of her contribution to public theology. The focus is upon how an evangelical community may be emancipated, especially in its desires and affections, from what O?Donovan sees as the distorting, even enslaving effects of liberalism's preoccupation with juridical subjective rights. It proceeds by taking up O?Donovan's challenge that theologians should be more alert to the meaning of what is ?public?. In this regard, it considers a striking feature of her account of evangelical public authority, which is her use of the term ?command?, when applied to the beliefs, affections, understanding and behaviour of those commanded. The connection between the church's commands and those made by a wide variety of social institutions and influences is considered. The significance of the distinction between jurisdictional and evangelical commanding is also examined in order to develop an account of evangelical affective culture and its practical consequences. In particular, this practical focus includes consideration of Eric Gregory's invitation to remark on what difference O?Donovan's approach makes with respect to the discussion of Christian nationalism.